Phase I study of the humanized anti-CD40 monoclonal antibody dacetuzumab in refractory or recurrent non-Hodgkin's lymphoma - Advani, Ranjana; Forero-Torres, Andres; Furman, Richard R; Rosenblatt, Joseph D; Younes, Anas; Ren, Hong; Harrop, Kate; Whiting, Nancy; Drachman, Jonathan G (Journal of clinical oncology, 2009)
To evaluate the safety, maximum-tolerated dose (MTD), pharmacokinetics, and antitumor activity of dacetuzumab in patients with refractory or recurrent B-cell non-Hodgkin's lymphoma (NHL). In this open-label, dose-escalation phase I study, dacetuzumab was administered to six cohorts of adult patients. In the first cohort, patients received 2 mg/kg weekly for 4 weeks; in all other cohorts, an intrapatient dose-escalation schedule was used with increasing doses up to a maximum of 8 mg/kg. Patients with clinical benefit after one cycle of dacetuzumab were eligible for a second cycle. In the 50 patients who received dacetuzumab, no dose dependence of adverse events (AEs) was observed. The most common AEs in >or= 20% of patients were fatigue, pyrexia, and headache; most were grade 1 or 2. Noninfectious inflammatory eye disorders occurred in 12% of patients. AEs grade >or= 3 occurred in 30% of patients and included disease progression, anemia, pleural effusion, and thrombocytopenia. Most laboratory abnormalities were grade 1 or 2; transient elevated hepatic aminotransferases occurred in 52% of patients. Two patients experienced dose-limiting toxicity: grade 3 conjunctivitis and transient vision loss in cohort (1), and grade 3 ALT elevation in cohort IV. The MTD of dacetuzumab was not established at the dose levels tested. Six objective responses were reported (one complete response, five partial responses). Tumor size decreased in approximately one third of patients. Dacetuzumab monotherapy was well tolerated in patients with NHL in doses up to 8 mg/kg/wk. Preliminary response data are encouraging and support additional studies of dacetuzumab in this patient population.